Spatial structure and regional development in China interregional input-output approach - Ihara Takeo; Okamoto Nobuhiro (Japan Institute of Developing Economies, 2004)
This book aims at 1st pay attentions to the recent spatial structure and regional development in China & 2nd show how to apply the most beneficial interregional input-output analysis to the various regional problems in China.
Keywords: China; Economic development